Congress Volume Edinburgh 1974 (1975)
Gld. 138; inter alia: J. C. L. Gibson, Myth, Legend and Folklore in the Ugaritic Keret and Aqhat Texts (37:561); A. Malamat, The Twilight of Judah: in the Egyptian-Вabylonian Maelstrom (37:723).